Monocarboxylate transport inhibition potentiates the cytotoxic effect of 5-fluorouracil in colorectal cancer cells. Issue 1 (28th August 2015) - Amorim, Ricardo; Pinheiro, Céline; Miranda-Gonçalves, Vera; Pereira, Helena; Moyer, Mary P.; Preto, Ana; Baltazar, Fátima
Abstract Cancer cells rely mostly on glycolysis to meet their energetic demands, producing large amounts of lactate that are extruded to the tumour microenvironment by monocarboxylate transporters (MCTs). The role of MCTs in the survival of colorectal cancer (CRC) cells is scarce and poorly understood. In this study, we aimed to better understand this issue and exploit these transporters as novel therapeutic targets alone or in combination with the CRC classical chemotherapeutic drug 5-Fluorouracil. For that purpose, we characterized the effects of MCT activity inhibition in normal and CRC derived cell lines and assessed the effect of MCT inhibition in combination with 5-FU. Here, we demonstrated that MCT inhibition using CHC (α-cyano-4-hydroxycinnamic acid), DIDS (4, 4′-diisothiocyanatostilbene-2, 2′-disulphonic acid) and quercetin decreased cell viability, disrupted the glycolytic phenotype, inhibited proliferation and enhanced cell death in CRC cells. These results were confirmed by specific inhibition of MCT1/4 by RNA interference. Notably, we showed that 5-FU cytotoxicity was potentiated by lactate transport inhibition in CRC cells, either by activity inhibition or expression silencing. These findings provide novel evidence for the pivotal role of MCTs in CRC maintenance and survival, as well as for the use of these transporters as potential new therapeutic targets in combination with CRC conventional therapy.